Reducing multiuser interference in the downlink transmission of MIMO broadcast system using STBC-DPC technique / Mohd Syarhan Idris - Idris, Mohd Syarhan (2017)
Space Time Block Code (STBC) technique can provide more benefit for mobile users with computational efficiency over the fading channel environment. Due to multiple transmit antennas requirement for the STBC system, it is hard to realize on mobile devices. It is always deployed on base station, also called downlink system. Based on the STBC downlink system, many literatures have proposed a double STBC system to acquire diversity gain and spatial multiplexing gain, simultaneously. However, it needs more computational complexity to combat the spatial interference at receiver. It will induce a heavy computation load for mobile user. In order to overcome the interference problem and reduce the computational loading for mobile user, this research investigated the precoding technique at base station, which can pre-cancel the spatial interference at base station. It is well known that the dirty paper coding (DPC) uses precoding technique to eliminate multiuser interference on single user or multiusers interference. Moreover, due to the DPC with interference free and low complexity benefits, this research propose the joint processing for single STBC and DPC (STBC-DPC) precoding techniques to acquire the spatial diversity and multiplexing gains. To the best of our knowledge, there is no publication paper which proposed joint single STBC and DPC precoding techniques for MIMO downlink systems. In this research, the MIMO STBC with four transmitter antennas and four receiver antennas is studied. To reduce the computational complexity at receiver, the STBC-DPC precoding technique is proposed to achieve the low computational complexity benefit for mobile station. Besides, to improve the performance of the proposed STBC-DPC system, the ordering LQ decomposition of channel matrix is proposed for the sequential one dimensional symbol detection. Simulation results confirmed that the proposed single STBC-DPC can reduce the multiuser interference which decreases the probability of error and achieves excellent BER performance of 70% with low computational complexity compared to double STBC-DPC.